2021
DOI: 10.1007/s13304-021-01042-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aspiration with sclerotherapy and laparoscopic deroofing for the treatment of symptomatic simple renal cysts: a systematic review and meta-analysis

Abstract: There are currently several strategies for the treatment of symptomatic simple renal cysts, such as aspiration with sclerosants and laparoscopic deroofing. However, no clear indication exists for choosing between them. Here, we carried out a systematic review and a meta-analysis of studies, which compared symptomatic and radiological success between aspiration with sclerotherapy and laparoscopic deroofing. Results were reported as relative risk (RR) and 95% confidence interval (95% CI) using laparoscopic deroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was reported that complications such as bleeding and infection were more common in the laparoscopic treatment group, and the operation time and hospital stay were prolonged as well. 12 Recently, pediatric literature also supports using sclerosing agent injection as the first option for symptomatic renal cysts before considering surgical intervention. 13 Additionally, Koenig et al presented a newborn with a giant renal cyst treated successfully with sclerosing agent treatment, which was treated successfully.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that complications such as bleeding and infection were more common in the laparoscopic treatment group, and the operation time and hospital stay were prolonged as well. 12 Recently, pediatric literature also supports using sclerosing agent injection as the first option for symptomatic renal cysts before considering surgical intervention. 13 Additionally, Koenig et al presented a newborn with a giant renal cyst treated successfully with sclerosing agent treatment, which was treated successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies are crucial for accurate diagnosis and management planning [2] . While laparoscopic deroofing is a well-established approach for symptomatic renal cysts, the finding of a MEST within such a cyst is exceedingly rare [3,4] .…”
Section: Introductionmentioning
confidence: 99%